A numerikus számítások szerepe a műszaki modellekben - Sipos, Dóra (International Journal of Engineering and Management Sciences, 2018)
Application of numerical methods and stochastic approach should have a bigger role in the Mathematics programme of the secondary schools. Studying economic and engineering problems leads to better understanding of the significance of mathematical models in practice. In our mini-course we introduce several topics related to mathematical modelling of systems and processes to present the applicability of mathematical calculation methods in the everyday life.